Analisis Penggunaan Database Dalam Sistem Informasi - Tiara Nurul (Merkurius : Jurnal Riset Sistem Informasi dan Teknik Informatika, 2023)
In today's modern era, every organization or business needs an information system, and it is used to improve information requirements, quality standards, and productive employee work. Organizations, institutions or businesses that have implemented an automated management system for all their administrative functions have also been encouraged to continue to do so by developing an information management system that integrates with or links to other components. Systems for managing information then help businesses integrate their own information, improve the quality of information they have access to, manage it effectively, and accelerate information processing so that routine tasks can be automated and innovated into business products that improve services and workflows. In this case, it can be said that management information systems and the technological capabilities they support have the potential to bring about significant changes in the economic and management fields.